What Happens When it's Windy in Denmark? An Empirical Analysis of Wind Power on Price Variability in the Nordic Electricity Market - Johannes Mauritzen (Research Institute of Industrial Economics (IFN), 2011)
High levels of wind power penetration will tend to affect prices in a deregulated electricity market. Much of the analysis in the literature has focused on the effect that wind power has on average electricity prices, this paper attempts to test the effect that wind power production has on the variability of wholesale electricity prices in the spot market. I use a simple distributed lag econometric model and five years worth of hourly and daily data from Denmark, which is one of the few places with a long history of significant wind power penetration. I show that wind power has the effect of reducing intra-day variability but that this result only partially carries over to price variation over weekly time windows. I suggest that the reduction in price variability in turn is due to a steeper supply schedule at peak-load times.
Keywords: C22; G30; L94; 330; Wind Power; Nordic Electricity Market; Empirical; Time Series; Windenergie; Strompreis; Warenbörse; Volatilität; Dänemark